2004
DOI: 10.1108/03090560410548924
|View full text |Cite
|
Sign up to set email alerts
|

The effect of word of mouth on services switching

Abstract: The effects of word of mouth (WOM) on the receiver's attitudes and intentions have been studied at length, but the question under which conditions WOM leads to a behavioural outcome (such as a purchase or switching decision) has received less attention. This paper studies the effects of WOM in the context of service provider switching. An empirical study is presented which researches whether perceived influence of a switching referral is related to subsequent switching behaviour, and whether the variables that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(160 citation statements)
references
References 29 publications
5
146
0
9
Order By: Relevance
“…Consumers may not be familiar with each other, but are essentially alike and have relatively equal intention or desire to give and receive the best information. Wangenheim and Bayon (2004) argue that source of similarity indicates the degree of similarity between the source of a recommendation and potential customers. Because individual consumers implicitly assume that similar people have similar preferences, they consider aggregated evaluations or opinions from others are informative and diagnostic (Chen, 2008).…”
Section: H2mentioning
confidence: 99%
“…Consumers may not be familiar with each other, but are essentially alike and have relatively equal intention or desire to give and receive the best information. Wangenheim and Bayon (2004) argue that source of similarity indicates the degree of similarity between the source of a recommendation and potential customers. Because individual consumers implicitly assume that similar people have similar preferences, they consider aggregated evaluations or opinions from others are informative and diagnostic (Chen, 2008).…”
Section: H2mentioning
confidence: 99%
“…WOM has extensively been studied in the marketing literature [2,5,20,21,40,62,65,66]. Studies have shown positive WOM to be an outcome of high customer satisfaction [59].…”
Section: Related Literature On Churn and Wommentioning
confidence: 99%
“…The ubiquity of internet access through, for example, smart phones, enables customers to vocalise their dissatisfaction very quickly after a negative service experience. This poses specific challenges to the management of negative UGC.The influence of WOM in services is well documented (Wangenheim and Bayon, 2004). WOM may help overcome the problem of intangibility of services by providing information from an experienced source (Bansal and Voyer, 2000) and may help shaping expectations of service (Zeithaml and Bitner, 2009).…”
mentioning
confidence: 99%